A cephalopod-inspired combustion powered hydro-jet engine using soft actuators. (April 2018) - Keithly, Dean; Whitehead, John; Voinea, Alexandra; Horna, Diego; Hollenberg, Samantha; Peck, Mason; Pikul, James; Shepherd, Robert F.
Abstract: Combustion in soft and compliant materials may enable new methods for underwater locomotion. Inspired by the motion of the soft bodied cephalopods, we developed a combustion-powered hydro-jet engine (CPHJE) using an expandable silicone bladder. The CPHJE used high energy density methane combustion to expand a silicone bladder and accelerate water into a hydro-jet that propelled the CPHJE. Cephalopods demonstrate the epitome of underwater soft robot capabilities. Their use of hydrojetting as a mode of high-speed underwater motion resembles high-power combustion events. This paper describes a soft combustion engine that propels a ∼ 0.7 kg body, with hydrodynamic surfaces in the likeness of an ellipsoid shaped squid, at instantaneous velocities of at least 0.8 m s −1 and single-pulse average velocities of 0.1 m s −1 . High-speed videography informs a model for the CPHJE's motion in time; the imaging also reveals that the hydrojetting generates a ring vortex. Tracking of this vortex results in an estimate that the working fluid is ejected in excess of 6.7 m s −1 . We demonstrate the CPHJE motion is both repeatable and able to produce multiple actuations with the same bladder. These results demonstrate a new method of underwater propulsion using combustion in soft and compliant bladders.